Resilience of S309 and AZD7442 monoclonal antibody treatments against infection by SARS-CoV-2 Omicron lineage strains - Case, James Brett; Mackin, Samantha; Errico, John M.; Chong, Zhenlu; Madden, Emily A.; Whitener, Bradley; Guarino, Barbara; Schmid, Michael A.; Rosenthal, Kim; Ren, Kuishu; Dang, Ha V.; Snell, Gyorgy; et al. (Nature communications, 2022)
Omicron variant strains encode large numbers of changes in the spike protein compared to historical SARS-CoV-2 isolates. Although in vitro studies have suggested that several monoclonal antibody therapies lose neutralizing activity against Omicron variants, the effects in vivo remain largely unknown. Here, we report on the protective efficacy against three SARS-CoV-2 Omicron lineage strains (BA.1, BA.1.1, and BA.2) of two monoclonal antibody therapeutics (S309 [Vir Biotechnology] monotherapy and AZD7442 [AstraZeneca] combination), which correspond to ones used to treat or prevent SARS-CoV-2 infections in humans. Despite losses in neutralization potency in cell culture, S309 or AZD7442 treatments reduced BA.1, BA.1.1, and BA.2 lung infection in susceptible mice that express human ACE2 (K18-hACE2) in prophylactic and therapeutic settings. Correlation analyses between in vitro neutralizing activity and reductions in viral burden in K18-hACE2 or human FcγR transgenic mice suggest that S309 and AZD7442 have different mechanisms of protection against Omicron variants, with S309 utilizing Fc effector function interactions and AZD7442 acting principally by direct neutralization. Our data in mice demonstrate the resilience of S309 and AZD7442 mAbs against emerging SARS-CoV-2 variant strains and provide insight into the relationship between loss of antibody neutralization potency and retained protection in vivo. SARS-CoV-2 variants of concern are less susceptible to therapeutic neutralizing antibodies, given mutations in the surface glycoprotein S. Here, Case et al. show that therapeutic antibodies S309 and AZD7442 reduce lung infection with SARSCoV-2 Omicron lineages in humanized mouse model despite the loss of neutralizing potency in vitro.